2021
DOI: 10.3126/jaim.v10i2.42175
|View full text |Cite
|
Sign up to set email alerts
|

Angiograhic profile and in-hospital outcome of young patients presenting with ST Elevation Myocardial Infarction (STEMI) in tertiary cardiac hospital

Abstract: Objective: To assess the angiographic profile and in hospital outcomes of primary percutaneous coronary intervention among young patients presenting with acute ST Elevation Myocardial Infarction and underwent primary PCI. Methods: The retrospective observational study was conducted at Shahid Gangalal National Heart Centre (SGNHC), Kathmandu, from july 2020 to June 2021, and included acute ST-Elevation Myocardial Infarction patients underwent primary percutaneous coronary intervention (PCI). Data was coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…The proportion of patients with RCA involvement ranged from 10.3% 25 to 58.6%. 22 Except for six studies, RCA involvement was more frequent than LCX involvement. Similarly, LCX was involved in 1.3% 63 to 51.0% 60 of the South Asian population.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The proportion of patients with RCA involvement ranged from 10.3% 25 to 58.6%. 22 Except for six studies, RCA involvement was more frequent than LCX involvement. Similarly, LCX was involved in 1.3% 63 to 51.0% 60 of the South Asian population.…”
Section: Resultsmentioning
confidence: 91%
“…21 Both the lowest and highest percentages of smokers in the South Asian study population were reported in India. Nepalese patients who were smokers were observed in 58.6% 22 to 80.8% 14 of the study population. Similarly, smoking was prevalent in 14.3% 23 to 64.7% 24 of Pakistani patients and in up to 77.4% 25 of Bangladeshi patients.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Самыми распространенным ФР у молодых являлись курение и дислипидемия, в то время как артериальная гипертензия (АГ) и СД встречались достоверно реже [4,5,10]. Также, по данным многих исследований, ожирение и отягощенная наследственность по сердечно-сосудистым заболеваниям достоверно чаще регистрируется у молодых пациентов с ИМ, однако в некоторых работах значимых различий выявлено не было [11,12]. Имеются данные, что в 20% случаев клиника ИБС в молодом возрасте обусловлена неатеросклеротическими факторами, такими как коронарные аномалии, дисплазии соединительной ткани и аутоиммунные заболевания [13].…”
Section: резюмеunclassified